PENCEGAHAN PERNIKAHAN DINI DAN PRODUKSI SAYURAN MANDIRI DI DUSUN PULAU PANJANG, DESA PENUTUK, KECAMATAN LEPAR PONGOK, KABUPATEN BANGKA SELATAN - Ardiansyah Kurniawan; Olivia Khanati; Eka Nurcahyono; Febi Kurniawati (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The people of Pulau Panjang, one of the islands in the South Bangka Regency, rely on capture fisheries for their livelihood. The problem in this area is the presence of non-economic by catch fish, including in districts with high early marriage rates, and the availability of vegetables that must be imported from other islands. Students of the Himpunan Kultur Akuatik carried out Village Development on Pulau Panjang to help solve the problem through aquaponics demonstration plots, counseling on early marriage, and joint activities. Counseling on early marriage and joint gymnastics was carried out with the enthusiasm of the residents, especially children. The aquaponics demonstration plot was successfully constructed using tarpaulin ponds and PVC pipes. The introduction of aquaponics was enthusiastically welcomed by the residents. Fish waste is used as fish feed. The demonstration plot management by the residents managed to start harvesting vegetables in the form of kale on the 27th day and reached a great harvest after 1.5 months. The success of the demonstration plot in vegetable production in an aquaponic system is expected to trigger the Pulau Panjang community to produce vegetables independently.